2016
DOI: 10.1007/s00396-016-3904-9
|View full text |Cite|
|
Sign up to set email alerts
|

The apparently anomalous effects of surfactants on interfacial tension in the IBA/water system near its upper critical solution temperature

Abstract: We studied the effect of anionic, cationic, and nonionic surfactants on the interfacial tension between the two phases of the isobutyric acid/water system using spinning drop tensiometry. It has been found that interfacial tension decreases with increasing concentration of the surfactant in the case of sodium dodecyl sulfate (SDS) and of dodecyltrimethylammonium chloride (DTAC). However, in the case of Triton X-100 an increase of surfactant concentration leads to an increase of the interfacial tension. Such re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…50 They can lower the interfacial tension due to their amphiphilic nature. 51 Therefore, we believe that the use of SDBS can improve the wettability of the support, promote monomer migration to the interface region, and enhance the efficiency of the polymerization. 52 First, the side of the modified nanofiber mats was contacted by the MPD solution for 300 s. Excess MPD solution was removed from the support surface using an air knife.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 They can lower the interfacial tension due to their amphiphilic nature. 51 Therefore, we believe that the use of SDBS can improve the wettability of the support, promote monomer migration to the interface region, and enhance the efficiency of the polymerization. 52 First, the side of the modified nanofiber mats was contacted by the MPD solution for 300 s. Excess MPD solution was removed from the support surface using an air knife.…”
Section: Methodsmentioning
confidence: 99%
“…Sodium dodecyl benzenesulfonate (SDBS), like sodium dodecyl sulfate, is a common type of surfactant . They can lower the interfacial tension due to their amphiphilic nature . Therefore, we believe that the use of SDBS can improve the wettability of the support, promote monomer migration to the interface region, and enhance the efficiency of the polymerization .…”
Section: Methodsmentioning
confidence: 99%
“…By measuring the drop radius and using Vonnegut’s formula (see below), he inferred the effective (transient) interfacial tension between the fluids. Similar measurements were performed by J. Pojman and co-workers, who investigated the existence of an effective interfacial tension (EIT) between miscible fluids and discussed its importance, using (i) mixtures of Isobutyric acid and water close to their critical point and (ii) dodecyl acrylate drops in poly­(dodecyl acrylate). They concluded that capillary forces are at work at the boundary between these fluids and quantified the EIT, again using Vonnegut’s theory.…”
Section: Introductionmentioning
confidence: 59%